The Logical Fallacy in Female Terrorists in Indonesia (Case Study: ISIS Period 2018-2023) - Damayanti, Anugrah Nia; Riyanta, Stanislaus (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
Terrorism represents a significant threat to both state and individual security. The effective combating of terrorism necessitates not only the implementation of repressive measures but also the fostering of societal resilience. The creation of societal resilience can be achieved by developing an intelligent society, thereby enabling it to combat the threat of radicalism and terrorism effectively. One way to foster societal resilience is to identify and address the logical fallacies of ISIS teachings. The authors selected the topic of female terrorists in Indonesia (ISIS case study 2018-2013 period) due to the increase in arrests of women related to terrorism following the Surabaya bombings in 2018. All of the women arrested are connected to ISIS. This paper employs the following theoretical frameworks: the informal logical fallacy theory (Van Vleet, Informal Logical Fallacies 2021), The Staircase to Terrorism (Mogadham, 2005), and Technic Analysis Counter Terrorism theory (Prunckun, 2010). The findings of the research indicated the presence of a logical fallacy among ISIS female terrorists. The logical fallacy observed in ISIS female terrorists in Indonesia can be attributed to the following factors: The indoctrination and education model employed by IS; the manipulation of religious teachings; the kinship system; the propagation of ideological narratives designed by IS; intense communication; the echo chamber and filter bubble; and women's psychological vulnerability all contribute to the phenomenon under study. The pattern of radicalization observed in ISIS female terrorists in Indonesia aligns with the theoretical framework of The Staircase to Terrorism (Fathali M. Moghadam). Counterterrorism measures must be implemented to address the logical fallacies observed in female terrorists. This necessitates a comprehensive approach encompassing prevention, preparation, response, and recovery.